INOVASI TEKNOLOGI BUDIDAYA PADI SAWAH YANG TELAH DAN SEDANG DIKEMBANGKAN DI SUMATERA BARAT DALAM RANGKA PENINGKATAN PRODUKTIVITAS PADI - Winardi Winardi (Universitas Muhammadiyah Purwokerto, 2014)
To achieve self-sufficiency in rice once a surplus of 10 million tons in 2014, one way could be reached by the application of technology. This review describes the rice cultivation technologies that have been and are being developed in West Sumatra by different institutions. Integrated Crop Management (ICM) is a technology recommendation of the Ministry of Agriculture. ICM in West Sumatra began in 2001. ICM technology is the integration of technological components, such as: young seedlings, seed quality, planting less than 3 plants per hill, new high yielding varieties, improved soil aeration with intermittent irrigation, the use of organic fertilizer, site-specific nutrient management through fertilizer N efficiency use LCC, as well as the use of P and K fertilizers based on soil nutrient status. Rice result achievement by ICM technology of various locations in West Sumatra is 5.30 to 7.25 t/ha. ICM has been implemented in the form of ICM-Field School in accelerating the deployment of technological innovation. SRI (The System of Rice Intensification) technology in pioneered by the Faculty of Agriculture, Andalas University since 2004. Four main components in the SRI are: the use of young seedlings, one seedling per planting point, plant spacing rare, and no stagnant water throughout the season. Increased productivity by SRI technolgy is mainly due to the increased number of productive tillers significantly, ie 40-80 plants per hill. Rice productivity achieved about 7.8 t/ha versus conventional farming productivity about 4.5 t/ha. Padi Tanam Sabatang/PTS (One-stem Planting Rice), is a rice-planting movement are programmed by the Agricultural Service of West Sumatra Province with District/City Agricultural Service all of West Sumatra. PTS that recommended since 2006 is actually a modification of the SRI technology. Component technologies that are emphasized include: the use of organic fertilizer, planting young seedlings one plant per hill, plant spacing of 30 x 30 cm or more, and the setting limited puddle during growth. Result achievement of rice with PTS technology about 7.0 t/ha. PTS has been applied to the level of Farmers Group or farmers through PTS-Field School. Keywords: lowland rice, crop cultivation, site-specific innovations, and West Sumatra.